Subungual glomus tumor: a clinical case and a review of the literature - Gameiro, Diogo; Fernandes, Fábio; Miraldo, Leonardo; Peixoto, Daniel; Ângelo, Susana (International Journal of Research in Orthopaedics, 2025)
Glomus tumors are rare vascular lesions, located in the dermis, very difficult to diagnose. A 55 years old female patient with pain at first finger of her right hand, which eradiated to the forearm, with several years of evolution. The pain was worst with local compression and cold exposure. The magnetic resonance imaging was compatible with a subungual glomus tumor. Surgical resection of the lesion by a lateral approach was done. The histopathological analysis confirmed the diagnosis and the patient complaints disappeared after the procedure. The surgical treatment is usually curative and the lateral approach, although not the most commonly used, could be a good alternative.